2016
DOI: 10.1016/j.bpj.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hematocrit on Platelet Adhesion: Experiments and Simulations

Abstract: The volume fraction of red blood cells (RBCs) in a capillary affects the degree to which platelets are promoted to marginate to near a vessel wall and form blood clots. In this work we investigate the relationship between RBC hematocrit and platelet adhesion activity. We perform experiments flowing blood samples through a microfluidic channel coated with type 1 collagen and observe the rate at which platelets adhere to the wall. We compare these results with three-dimensional boundary integral simulations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…The risk of VTE in the Tromsø and ARIC general population studies, however, appears to be increased at hematocrit levels much lower than for polycythemia vera. Mechanistically, high hematocrit increases platelet margination and adhesiveness . However, a more important mechanism by which hematocrit may increase VTE risk is via increased blood viscosity and venous stasis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of VTE in the Tromsø and ARIC general population studies, however, appears to be increased at hematocrit levels much lower than for polycythemia vera. Mechanistically, high hematocrit increases platelet margination and adhesiveness . However, a more important mechanism by which hematocrit may increase VTE risk is via increased blood viscosity and venous stasis …”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, high hematocrit increases TA B L E 3 Hazard ratios (95% CIs) of total, provoked, and unprovoked VTE by groups of Visit 1 hematocrit, ARIC, 1987-1989 through 2015 Hematocrit (percentiles based on sex-race specific cut points) platelet margination and adhesiveness. [20][21][22] However, a more important mechanism by which hematocrit may increase VTE risk is via increased blood viscosity and venous stasis. 1,23 A previous population-based control study suggested iron deficiency anemia is associated with a 40% increase in VTE, 24 and, although not statistically significant, spline analysis in the Copenhagen Study suggested that VTE may be elevated in those with low hematocrit.…”
Section: Discussionmentioning
confidence: 99%
“…However, data to support the use of fresh red blood cells preferentially for critically-ill patients is lacking (74). Hematocrit also contributes to platelet margination to the vessel wall under flow and low hematocrit is associated with increased bleeding time (75,76). …”
Section: Blood Transfusion To Treat Blood Failurementioning
confidence: 99%
“…This layer is known to contribute in the reduction of the blood viscosity or plasma skimming as blood perfuses the smaller vessels (Freund, 2014;Pries and Secomb, 2003). In addition, the migration of the red blood cells induces the margination of stiffer platelets by volume exclusion (Spann et al, 2016;Fitzgibbon et al, 2015;Reasor et al, 2013;Vahidkhah, 2015;Haga et al, 1998;Bächer et al, 2018). These marginated platelets are now better located to participate in reactions with the endothelial cells in the event of an injury when the clotting cascade begins (Mitrophanov et al, 2014;Govindarajan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%